THE USE OF TIC TAC TOE GAME IN TEACHING SPEAKING SKILL - Hidayati Hidayati (Linguistics and ELT Journal, 2015)
This study was carried out to find the effect of of tic tac toe game in teaching speaking skill. This study was conduced at the second grade of MAN 1 Praya in academic year 2014- 2015. The total number of sample were 40 students and they were divided into two groups. The first group was called experimental group consist of 20 students and the second group was called control group consist of 20 students. After analyzing the data obtained , the researcher found that the use of tic tac toe game has effect in teaching speaking skill. It proved from the data analysis, the researcher found that the value of t-test was 6,3, while the value of t-table in df 38 were 2,024 for confidence level 0,05 (90%) and 2,71 for confidence level 0,01 (99%). It showed that the value of t-test is higher than t-table. It is mean that the use of tic tac toe game has effect in teaching speaking skill. So, the null hypothesis (Ho) was accepted because the use of tic tac toe game has effect in teaching speaking skill at the seond grade of MAN 1 Praya in Academic Year 2014- 2015.